INFLUENCE OF ONLINE CONSULTATION SERVICE QUALITY ON PATIENT'S TRUST SPORT MEDICINE SPECIALIST DOCTOR AT MELINDA 2 HOSPITAL BANDUNG - Alvin Wiharja; Euis Eka Parmiasih; Yuyus Suryana (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2022)
This study aims to determine and analyze the effect of the quality of online consultation services on the patient's trust in sports medicine specialists at Melinda 2 Hospital Bandung. The results of the study can be used as a recommendation for hospital management in improving the quality of online consulting services. The research method used is descriptive analysis and verification. The data collection used is a questionnaire accompanied by observation techniques and literature, Sampling using saturated sampling. Data collection in the field was carried out in 2022. The data analysis technique used path analysis. The results showed that there was an influence on the quality of online consulting services consisting of physical evidence, reliability, responsiveness, assurance and empathy on patient trust in sports medicine specialists at Melinda 2 Hospital Bandung.